Exploration of probiotic attributes in lactic acid bacteria isolated from fermented Theobroma cacao L. fruit using in vitro techniques - Nandha, Mausamy C.; Shukla, Rachana M. (Frontiers in Microbiology, 2023)
The current investigation delves into the primary characterization of lactic acid bacteria obtained from the Indian-origin Theobroma cacao L. Forestero variety. Out of the 11 isolates studied, 5 demonstrated classical LAB traits. The entire set of five isolates exhibited robust resilience against both acid and bile salts, pivotal prerequisites for potential probiotic applications. Notably, among these isolates, CR2 emerged as a standout candidate with maximal bile salt hydrolase activity, phenol, and lysozyme resistance. These promising findings were consistently upheld when subjecting the isolates to simulated gastric and pancreatic fluids, along with lysozyme exposure, wherein CR2 and CYF3 exhibited notable survival rates. The isolates displayed variable degrees of auto-aggregation, co-aggregation, and hydrophobicity with xylene and chloroform. Of paramount importance, the production of exopolysaccharides was most prolific in CR2 (0.66 mg/mL), implying a capacity for biofilm formation and ecological adaptation. The inhibitory potential of α-glucosidase, an enzyme linked to glucose metabolism, ranged from 12.08% to 56.55%, with CR2 manifesting the highest inhibition rate. Furthermore, antioxidant activity was notably substantial, demonstrated by scavenging percentages of 79.62% (DPPH) and 83.45% (ABTS) for the CR2 isolate. The safety assessment underscored the non-pathogenic nature of the isolates, reaffirming their suitability for probiotic applications. Molecular characterization validated CR2 as Lactococcus lactis subsp. lactis and CYF3 as Limnosilactobacillus fermentum. Both strains exhibited commendable probiotic and technological attributes, surpassing their counterparts. This study offers valuable insights into the realm of potential probiotic candidates sourced from Indian Theobroma cacao L., characterized by a constellation of advantageous traits. The observed attributes, ranging from survival in hostile conditions to beneficial enzymatic activities and bioactivity, position these isolates as promising candidates for future applications in functional foods and beyond.